Peningkatan Keterampilan Menulis Teks Dengan Metode Diskusi Berbantuan Media Flashcard pada Siswa Kelas 3 SD Negeri Bandungan 01 - Riswari, Ardana; Sutomo, Dr; Wijayanti, Atrianing Yessi (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2024)
This research was motivated by the low level of students' text writing skills in the Indonesian language subject, writing skills material in class 3 of Bandungan 01 State Elementary School, Bandungan District. The formulation of the problem in this research is whether the application of the discussion method using flashcard media can improve the descriptive text writing skills of 3rd grade students at SD Negeri Bandungan 01, Bandungan District, Semarang Regency? This research aims to find out whether the discussion method using flashcard media can improve the descriptive text writing skills of grade 3 students at SD Negeri Bandungan 01, Bandungan sub-district, Semarang Regency.The research method used was Classroom Action Research (PTK) taking as subjects 3rd grade students at Bandungan 01 State Elementary School. This research was carried out in the 2023-2024 school year from October to November 2023 using the 2013 Curriculum. Text writing skills were measured based on the percentage of score achieved. write text. The research implementation procedure was carried out in two cycles. The data collection technique for this research is by assessing the writing skills of grade 3 students, observing teacher skills, and observing student activities during the learning process. The data analysis used was an assessment of grade 3 students' writing skills, data analysis of teacher skills and analysis of student activities.The research results showed that the percentage of achievement in improving students' writing skills in cycle I was 43.33%, while in cycle II it was 83.33% in the very good category. The increase in teacher skills in teaching in the first cycle was 63.8%, including the sufficient category, and experienced an increase in the second cycle of 88.80% in the very good category. The same thing happened to student activities, namely in cycle I student activity was 40% (fair) to 83.3% (very good) in cycle II. Thus it can be concluded that the discussion method uses flashcard media can improve the writing skills of class III students at SD Negeri Bandungan 01.Keywords: writing skills, discussion methods, and mediaflashcard.